Knowledge and Practice of Menstrual Hygiene and Reproductive Tract Infection in Adolescent Girls in Doda District of Jammu and Kashmir Territories, India - Suresh Kotwal; Garima Charak; Sudeep Kumar; Sudhanshu Shekhar; Kasturi Lal Gupta (International Journal of Integrated Health Sciences, 2022)
Objective: To assess knowledge and practices regarding menstrual hygiene and reproductive tract infection in adolescent girls in Doda District of Jammu and Kashmir Territories, India.Methodology: This cross-sectional study was performed on adolescent girls attending schools in Doda district of Jammu and Kashmir territories, India. Data were collected through interviews using a predesigned semi-structured questionnaire and results were analyzed using MS Excel.Results: A total of 450 adolescent girls from public and private schools of Doda district of Jammu and Kashmir were included in this study. Most participants were in the 14-16 years of age. The most common source of information about menstruation identified in this study was mother (56.2%), sister (13.1%), teacher (12.7%), and friends (9.6%). In terms of menstrual hygiene, 53.1% girls used sanitary pads, 24% girls used dry cloths/towel and 10.7% girls used homemade and sanitary pads during their menstrual period. About 42% of the participant were absent from school during their menses and most participants take daily bath during their menses.Conclusion: Awareness regarding menstruation and menstrual hygiene needs to be improved with the emphasize on providing accurate and adequate information on this topic to adolescent girls. Information and provision on affordable absorbent napkins or pads during menstrual period are also important for these girls.